The Application of Radiofrequency Waves in Supportive Treatment of Temporomandibular Disorders - M. Pihut; M. Górnicki; M. Orczykowska; E. Zarzecka; W. Ryniewicz; A. Gala (Pain Research and Management)
In recent years, the number of patients applying for prosthetic treatment due to temporomandibular joint disorders (TMD) has been increasing. The main methods for treating disorders are the use of occlusal splints and physiotherapeutic rehabilitation as supportive treatment. Radio waves are electromagnetic waves with radiation frequency between 3 Hz and 3 THz, used for physiotherapeutic treatment of skeletal muscle relaxation in the range of 3 to 6 MHz. The rehabilitation effect of these waves is based on diathermy by means of high-voltage quick alternating current. Aim. The aim of the study was to evaluate the influence of radiofrequency waves on the pain of the masticatory muscles in the course of TMD and the usefulness of these procedures in the supporting treatment of these disorders. Materials and Methods. Patients aged 19 to 45 years, of both sexes, reported to the Consulting Room of TMD at the Institute of Dentistry in Krakow to undertake prosthetic treatment of TMD (I a—according to RDC/TMD). Study group (SG) consists of 20 patients who had 10 supportive treatments with radiofrequency currents. In the case of application of radiation to the muscle area, the energy was 20 J to the area of the masticatory muscles, the frequency was 3 MHz, bipolar technique, the duration of the procedure was 10 minutes, and the coupling substance was a gel for ultrasound examinations. The control group (CG) consisted of 20 patients who had 10 supportive treatments with sonophoresis procedures. For the area of masticatory muscles, 0.9 W/cm2 treatments were applied, the duty factor was 80%, the treatment time was 10 minutes, and the medical substance was 25% Voltaren gel. Results. Analysis of the results of the first clinical examinations (axis I) conducted in both groups shows a homogeneous clinical material and similar results. The second clinical examination revealed improved clinical parameters, but it showed a greater improvement in the SG. In the SG, the mean level of VAS was 6.25, and the extreme values were 5.9–0.14, the median was 2.15, and the standard deviation was 1.54. In the CG, the average value of VAS was 6.20 (peak of 5.2–0.7), the median was 2.4, and the standard deviation was 1.87. Summary. The search for new methods of supportive treatment of TMD is an important research direction due to the complex etiology of this disease and the lack of an explicit treatment algorithm. Conclusion. The results of our own research clearly indicate that the use of the radiofrequency waves brings pain relief and improvement of clinical parameters to a greater extent than in sonophoresis. It can be a very important new method in supportive treatment of TMD. Research needs to be continued.